Concentração do suco de uva utilizando processos com membranas - Campos, Plínio Ribeiro Fajardo (2012)
In this work a combination of both reverse osmosis and ultra filtration processes to obtainment a concentrated grape juice with the same characteristics as found in nature grape juice was investigated. As raw material for all tests Isabella grape that is one of the most important varieties of Vitis labrusca originated from the South of the United States was used. By a previous crushing process the grape pulps were obtained, and then washed, packaged and stored in freeser storage for a posterior treatment. A centrifugation process followed by an enzymatic treatment for reducing the levels of suspended solids and pectin were performed on the grape pulps. By using a micro/ultra tangential filtration system, which was operated at two temperatures values of 30 and 40 oC, three pressure values of 1, 2 and 3 bar, and membranes with pore sizes of 0.05, 0.1 and 0.2 μm, a set of clarified grape juice samples was obtained. Afterwards a reverse osmosis process (ROP) based on a spiral membrane of composed film and operated at a pressure of 40 bar, a temperature value of 30 and 40 oC was applied on all clarified grape juice samples. Analyzing the set of physico-chemical parameter values, a reduction mainly on the values of turbidity and color was observed on the ultra-filtrated grape juice samples. When the micro/ultra-filtration system was operated at a pressure value of 1 bar and a temperature value of 40 oC, it was observed that the membrane of 0.05 mm has become a divisor of grape juice flow according to the analysis of the mean permeated flow that was stable during the filtration process. Under this filtration experimental condition, the values of permeated grape juice sample flows can be considered high as compared with those reported in the literature, achieving a flow value of 136.38 kg m-2h-1 for better experimental condition. From the fitting of experimental data, a value of 124.51 kg m-2h-1 for the permeated grape juice sample flow was attained. By applying the ROP (reverse osmosis process) keeping fixed the temperature at 30 oC, the mean flow values of permeated grape juice containing water were of 19.70, 26.4 and 33.11 kg m-2h-1 for pressure values of 20, 30 and 40 bar, respectively. After the stabilization of the mean grape juice flow under a pressure of 40 bar, mean grape juice flow values of 8.35 and 4.65 kg m-2h-1 for temperatures of 30 and 40 oC, respectively. It can be noticed that an increasing of temperature has accentuated the fouling phenomenon. Performing a comparison between fitting and experimental parameters, the highest value of critical grape juice flow was attained when the ultra filtration system was operated at a temperature of 40 oC and a pressure of 1 bar and using a membrane with pore size of 0.05 μm. Such critical grape juice flow is equivalent to the mean one experimentally found, suggesting a good agreement with the experimental data. The micro/ultra filtration based clarification process of grape juices that were enzymatically treated was efficient to remove the suspended particulates and reduce the turbidity, resulting in a grape juice with higher transparence and the absence of grape pulps. Therefore, the reverse osmosis process could be potentially considered as a good alternative on the grape juice concentration.